FESTA. Handbook version 2 - FESTA Consortium (2008)
In Japan and in the United States Field Operational Tests (FOTs) have been introduced as an evaluation method for driver support systems and other functions several years ago with the aim of proving that such systems can deliver real‐world benefits. In Europe too, FOTs have been conducted at a national or regional level, particularly on speed support systems and lane departure warning systems. These FOTs have proven to be highly valuable. Recently FOTs have been identified as an important means of verifying the real‐world impacts of new systems at a European level and in particular to verify that European R&D has the potential to deliver identifiable benefits. This Handbook is the result of a joint effort of several research institutes, OEMs and other stakeholders from across Europe to prepare a common methodology for European FOTs. It is also highly relevant, and it is hoped useful, for FOTs conducted at a regional or national level within Europe as well as outside Europe.